Factors influencing non-tax revenue sustainability in Indonesian government institutions: the mediating role of accountability - Puji Wibowo; Etty Murwaningsari (Cogent Business & Management, 2024)
Non-tax revenue (NTR) is a source of national revenue that has significantly grown over the last two decades in Indonesia. Apart from the achievement of NTR in the national budget which shows a positive trend, there are still accountability issues that were disclosed by the Supreme Audit Agency in the audit findings of the central government's financial reports. This study aims to analyze the factors that promote the sustainability of NTR as potential central government revenue by placing accountability as a mediating variable. This quantitative research uses a survey approach to collect data by distributing questionnaires across central government institutions. Respondents who are the object of research are civil servants who work in State Ministries/Institutions with certain criteria. The data collected for this study were 353 respondents, mainly from the 20 national government agencies that were the largest NTR generators in the last three years. The partial Least Square-Structural Equation Modeling (PLS-SEM) was utilized to analyze the data. The results of the study show that government internal control and accountability have proven to be favorable for creating NTR sustainability. Accountability is an effective mediating factor for sustainable leadership and human resource (HR) competencies in supporting the strengthening of NTR sustainability. This research provides policy implications for central government institutions to strengthen accountability by internalizing accountability principles in NTR management, enhancing the internal control level, and formulating talent management for better government officer promotion designThis research explores factors influencing non-tax revenue sustainability across Line Ministries and Agencies in Indonesia by incorporating accountability as a mediating variable in our model. The study also develops new measurements of sustainability and accountability within a non-tax revenue context. Findings provide that government internal control directly influences non-tax revenue sustainability. Meanwhile, sustainability leadership and human resource competency affect non-tax revenue sustainability through accountability. Our research reveals that non-tax revenue accountability matters in explaining non-tax revenue sustainability. This research proposes a new measurement of non-tax revenue sustainability by adding three dimensions, namely strategic planning, spending management, and budgeting performance quality. The measurement is proven better than the old model recommended by International Public Sector Accounting Boards (2013) The study also indicates that a new measurement for non-tax revenue accountability is more robust than Han and Perry's (2019) model, by incorporating two dimensions, of political and spiritual aspects. Our research provides insights for central government institutions to maintain individual accountability to promote non-tax revenue sustainability for better national budget quality.
Keywords: M41; M48; 650; Accountability; leadership; line ministries and agencies; non-tax revenue; fiscal sustainability